IMPLEMENTASI KEGIATAN PEMBIASAAN KARAKTER ASWAJA (PKA) DALAM MENINGKATKAN LITERASI KEAGAMAAN SISWA DI MI NU WALISONGO SUMBERREJO - Midya Yuli Amreta; Alif Via Rahmawati; Putri Indah Puspita; Nurul Khofifah Tuni’mah; Dwi Setya Ningsih; Anisa Auliya Febriyanti; Saskia Agustina (STKIP Pesisir Selatan, 2026)
This research is motivated by the importance of strengthening students' religious literacy through the instillation of Nahdlatul Ulama’s amaliah values, particularly through activities integrated between character habituation and reading activities. The Character Habituation of Aswaja (PKA) activities at MI NU Walisongo Sumberrejo are one of the efforts to improve students' religious literacy skills while shaping a religious character based on the values of Ahlussunnah wal Jama’ah. This study aims to describe the implementation of PKA, the forms of religious literacy activities carried out, and their impact on students' ability to read, understand, and practice religious teachings. The research method used is qualitative with data collection techniques through observation, interviews, and documentation. The research results show that PKA activities are carried out routinely every morning before learning through literacy-based religious activities, such as reading prayers together, sholawat, tahlil, diba’, istighotsah, as well as readings in prayer that are done repeatedly and in a directed manner. These activities have been proven to improve students' reading skills, broaden religious understanding, and encourage the internalization of the values of tawassuth, tawazun, tasamuh, and i’tidal in daily life.